Oral and maxillofacial tumours surgically treated at Muhimbili National Hospital, Dar es salaam, Tanzania: experience over 5 years. (Tanzania Medical Journal, 2010)
Bacground: Tumours that affect the oral and maxillofacial region originate from odontogenic or non odontogenic tissues. They possess varying clinical and histopathological characteristics based upon which they are regarded as either benign or malignant. Objective: To report on the demographic, diagnosis, treatment and prognosis of oral and maxillofacial tumours surgically treated at Muhimbili National Hospital (MNH), Dar es Salaam, over a five year period. Methodology: For every patient demographic data (i.e. age, sex, address and occupation), histopathological diagnosis, duration of the disease and the details of the treatment procedure done were recorded in a special form. Treatment details included the type of surgery i.e. enucleation, excision or resection with or without reconstruction. The patients were recalled for assessment of their conditions postoperatively at three, six and twelve months interval. Data was entered into computer using the Epi-info programme. Statistical analysis for significance was calculated with p≤ 0.05. Results: A total of 148 patients, 60 (40.5%) males and 88 (59.5%)females aged between 6 and 70 years with a mean of 25.8 years (SD= 16.4) were included in the study. Ameloblastoma was the commonest tumour encountered in 46 (31.0%) patients, followed by ossifying fibroma 19 (12.8%) and pleomorphic adenoma in 20 (13.5%) patients. Other tumours in this group of patients included giant cell tumour in 11 (7.4%) patients, myxoma 10 (6.8%), fibrous dysplasia 9 (6.1%) and haemangioma in 7 (4.7%) patients. Twentysix(17.6%) patients had tumours that appeared with very low frequencies therefore, these were grouped together as others. The surgical approaches differed according to histological types and clinical characteristics of the tumours. Except for two patients with ameloblastoma who got infection, all surgical wounds healed uneventfully. Conclusion: Ameloblastoma was the commonest encountered tumour in this group of patients. Majority of the patients presented rather late with massive tumours that needed ablative surgery. A national programme focusing on early detection and definitive treatment of these tumours, including health education addressed to the public, general and oral health professionals is important.